If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60x + 75y = 9 Solving 60x + 75y = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75y' to each side of the equation. 60x + 75y + -75y = 9 + -75y Combine like terms: 75y + -75y = 0 60x + 0 = 9 + -75y 60x = 9 + -75y Divide each side by '60'. x = 0.15 + -1.25y Simplifying x = 0.15 + -1.25y
| -8+n=-7 | | (-11)-w=(-36) | | 4x-3-7=-27 | | x-(-15)=10 | | 2y-20=35 | | 4x+7+2x=-5x | | -8(9k+7)=15+3k | | 6x-8x+10=9x+19+13 | | r+8=22 | | 5x+2(x-3)+2x=6x+3(x+2)-4+x | | x+y-24=0 | | 12m=240 | | -12x-2y=-54-3x | | Kx+13-8x=-1 | | -7d-2d=-33 | | -2x+3=.5x+3 | | 2x^2=7x-29 | | 17+a=8 | | 3x-7y=6-5y | | 20n=180 | | 1=X-2x^2 | | 3d=9d-9 | | 29-3c=9(7c+2) | | 6=7y+3 | | 6r-12=3+7r | | -20b=280 | | 345-4532x=12 | | 3y+2-4=6 | | 8x=16x+24 | | 2(6-2y)+4y=12 | | -5(1+6r)=22 | | 60*60*0+1= |